(untitled) (Jurnal Manajemen Bisnis, 2023)
In the age of technological disruption, new technology has brought about many developments. The PR industry is affected by this disruption of old industries, markets, and processes. The rapid adoption of new PR technologies forces staff to be more adaptable. Artificial intelligence enters public relations. PR is fast shifting from traditional to digital PR with AI. AI and PR can collaborate on work. With the rise of AI in daily life, Indonesian public relations uses Media Monitoring. Public Relations professionals employ automated media monitoring to gain faster and more useful information. AI (Media Monitoring) techniques in PR are tested for user experience in Indonesian multinational private enterprises. Structured participant interviews are utilised for qualitative research. The results show that PR’s transformation in Indonesia has changed PR practises; the use of AI technology in PR activities has had a positive impact; although AI technology is sophisticated and can transform various jobs, AI cannot replace the primary role of humans, especially in PR work; and the use of AI tools, such as media monitoring, has increased efficiency and effectiveness.